HUBUNGAN INDIKATOR KEMISKINAN DENGAN KEPEMILIKAN SANITASI LAYAK DI PROVINSI GORONTALO TAHUN 2010 (Data Sekunder Riskesdas Tahun 2010) - Raharyanti, Fenny (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2013)
The study explores the determinants of proper sanitation, ownership of various indicators of poverty in the province of Gorontalo, 2010, with the source data comes from the Riset Kesehatan Dasar 2010. Selection of this province based on the highest position in terms of sanitation facilities and the open defecation which is 39.2% and 41.7%, beside it is the fourth lowest poverty line in Indonesia . This is a quantitative research with a cross sectional design. The research concluded that significant poverty indicators relating to the ownership of proper sanitation as multivariable are defecation facilities, drinking water, followed by housing conditions (type of wall and floor type), income, employment and education